Compositionchimiqueetpropriétésantimicrobiennes de l’huile essentielle d’une espèce aromatique :Pituranthos scoparius - CHABBI Chaima; GHAZI Lamia (My University, 2026)
This study, conducted within the framework of the MEDICINOM 2026 research project of the Medicinal Plants Research Unit (URPM) of Laghouat, focused on the chemical characterization and biological evaluation of the essential oil of Pituranthos scoparius (Apiaceae). The essential oil was obtained by hydrodistillation with a yield of 0.28%. Gas chromatography–mass spectrometry (GC–MS) analysis enabled the identification of 63 compounds representing almost the entire volatile fraction of the essential oil. The chemical profile was dominated by hydrocarbon monoterpenes, particularly α-pinene (33.96%), trans-β-ocimene (9.44%), sabinene (8.79%), β-pinene (7.69%), and α-thujene (5.99%), classifying this essential oil as an α-pinene-rich chemotype. The antidiabetic activity assessed through the α-amylase inhibition assay revealed a weak inhibitory effect, preventing the determination of an IC50 value. Antioxidant activity evaluated using the DPPH and FRAPS assays showed moderate activity, with values of 1.11 ± 0.14 mg vitamin E equivalent/g oil and 3.46 ± 0.95 mg vitamin E equivalent/g oil, respectively. Antimicrobial activity evaluation demonstrated selective sensitivity among the tested microorganisms. The essential oil exhibited notable antibacterial activity against Escherichia coli and Pseudomonas aeruginosa, with minimum inhibitory concentrations (MICs) of 0.01 mg/mL and 0.021 mg/mL, respectively, whereas no activity was observed against Staphylococcus aureus and Bacillus subtilis.The obtained results highlight the chemical richness of P. scoparius essential oil and emphasize its promising antimicrobial potential. This study contributes to the valorization of this Algerian medicinal species and provides a basis for future investigations aimed at isolating bioactive compounds, elucidating their mechanisms of action, and evaluating their efficacy through in vivo studies. ----------------------------------------------------------------------------------------------------------------------------------------------------------------------- أنجزت هذه الدراسة في إطار مشروع البحث MEDICINOM 2026 التابع لوحدة البحث في النباتات الطبية (URPM) بالأغواط، وهدفت إلى التوصيف الكيميائي وتقييم الأنشطة البيولوجية للزيت العطري لنبات Pituranthos scoparius المنتمي إلى الفصيلة الخيمية (Apiaceae). تم الحصول على الزيت العطري بواسطة التقطير المائي بنسبة مردود بلغت 0.28%. أتاح التحليل بواسطة كروماتوغرافيا الغاز المقترنة بمطيافية الكتلة (GC-MS) التعرف على 63 مركبًا كيميائيًا تمثل تقريبًا كامل الجزء المتطاير من الزيت العطري. وأظهرت النتائج سيادة المونوتربينات الهيدروكربونية، حيث كان α-بينين (33.96%) المركب الرئيسي، يليه trans-β-ocimene (9.44%)، وsabinene (8.79%)، وβ-pinene (7.69%)، وα-thujene (5.99%)، مما يصنف هذا الزيت العطري ضمن النمط الكيميائي الغني بـ α-بينين. أظهر تقييم النشاط المضاد للسكري، من خلال اختبار تثبيط إنزيم α-amylase، فعالية تثبيطية ضعيفة، إذ لم تسمح النتائج بتحديد قيمة IC50. أما النشاط المضاد للأكسدة، الذي تم تقييمه باختباري DPPH وFRAP، فقد أظهر فعالية متوسطة، حيث بلغت القيم 1.11 ± 0.14 و3.46 ± 0.95 ملغ مكافئ فيتامين E/غ من الزيت على التوالي. كما أظهر تقييم النشاط المضاد للميكروبات حساسية انتقائية للكائنات الدقيقة المختبرة، إذ سجل الزيت العطري نشاطًا ملحوظًا ضد Escherichia coli وPseudomonas aeruginosa بقيم التركيز المثبط الأدنى (MIC) بلغت 0.01 و0.021 ملغ/مل على التوالي، في حين لم يُظهر أي نشاط ضد Staphylococcus aureus وBacillus subtilis. تُبرز النتائج المتحصل عليها الغنى الكيميائي للزيت العطري لنبات Pituranthos scoparius وتؤكد إمكاناته الواعدة، خاصة فيما يتعلق بنشاطه المضاد للميكروبات. كما تساهم هذه الدراسة في تثمين هذا النبات الطبي الجزائري وتشكل أساسًا لأبحاث مستقبلية تهدف إلى عزل المركبات الفعالة حيويًا، وفهم آليات عملها، وتقييم فعاليتها من خلال الدراسات داخل الكائن الحي (In vivo). ------------------------------------------------------------------------------------------------------------------------------------------------------------------------ Cette étude, réalisée dans le cadre du projet de recherche MEDICINOM 2026 de l’Unité de Recherche sur les Plantes Médicinales (URPM) de Laghouat, a porté sur la caractérisation chimique et l’évaluation des activités biologiques de l’huile essentielle de Pituranthos scoparius (Apiaceae). L’huile essentielle a été obtenue par hydrodistillation avec un rendement de 0,28 %. L’analyse par chromatographie en phase gazeuse couplée à la spectrométrie de masse (GC-MS) a permis d’identifier 63 composés dominés par les monoterpènes hydrocarbonés, notamment l’α-pinène (33,96 %), le trans-β-ocimène (9,44). Les tests antioxydants DPPH et FRAP ont mis en évidence une activité modérée avec des valeurs respectives de 1,11 mg équivalent vitamine E/g d’huile et 3,46 mg équivalent vitamine E/g d’huile. L’évaluation de l’activité antimicrobienne a montré une sensibilité sélective des microorganismes testés. L’huile essentielle a présenté une activité notable contre Escherichia coli et Pseudomonas aeruginosa avec des concentrations minimales inhibitrices de 0,01 g/mL et 0,021 g/mL, respectivement, tandis qu’aucune activité n’a été observée contre Staphylococcus aureus et Bacillus subtilis. L’activité antidiabétique évaluée par le test d’inhibition de l’α-amylase n’a révélé aucune capacité inhibitrice. Cette étude contribue à la valorisation de cette espèce médicinale algérienne et constitue une base pour de futures investigations portant sur l’isolement des composés actifs, l’étude de leurs mécanismes d’action et l’évaluation de leur efficacité in vivo.
Keywords: Pituranthos scoparius; essential oil; GC–MS; α-pinene; antimicrobial activity; antioxidant activity; antidiabetic activity.; الزيت العطري، GC-MS، α-بينين، النشاط المضاد للميكروبات، النشاط المضاد للأكسدة، النشاط المضاد للسكري; huile essentielle; GC-MS; activités biologique